The location of Ti containing phases after the completion of the NaAlH4 + xTiCl3 milling process - Pitt, M.; Vullum, P.; Sørby, M.; Blanchard, D.; Sulic, M.; Emerich, H.; Paskevicius, Mark; Buckley, Craig; Walmsley, J.; Holmestad, R; Hauback, B. (Elsevier B.V., 2012)
The NaAlH4 + xTiCl3 (x < 0.1) system has been studied by X-ray synchrotron diffraction and transmission electron microscopy (TEM) after the completion of the milling process, for both planetary (PM) and cryo milled (CM) samples. Comparison of the NaAlH4 mosaic size (coherence length) determined from the X-ray synchrotron diffraction lineshape, and measurement of the external powder grain dimensions of ca. 250–300 particles by TEM, reveals that after the completion of the milling process, (1 1 0) {1 1 1} edge dislocated 2–20 nm Al crystallites are dispersed in a Ti rich amorphous (a-)Al1−xTix (0.3 < x < 0.5) matrix. This nano Al/Al50Ti50 composite is embedded on the surface of single crystalline NaAlH4 powder grains. The NaAlH4 single crystal powder grains are moderately defected with uncorrelated defects, induced from the milling process.